WATER AS INSPIRATION OF AUGMENTED REALITY CORAL SPONGES: INFORMATION AND EDUCATIONAL MEDIA - I Komang Try Adi Stanaya; I Gst. Ngr. Dwijaksara (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
"Toya", the Sanskrit for water, has an excellent value for the survival of living things in the world. Around 71% of the earth's surface is covered by water, whereas the oceans hold about 96.5% of all water. The sea is currently affected by contamination from waste or garbage such as plastic, metal, glass, wood, paper, rubber, clothing, and textiles. The lack of public awareness of maintaining environmental cleanliness contributes to trash accumulation in the ocean, which also impacts marine ecosystems. One part of the marine ecosystems affected by marine trash is coral sponges through the implementation of augmented reality (AR) based science technology by creating applications that can be used as a medium of information about coral sponges in the form of three-dimensional (3D) objects, as well as a tangible layout of providing education about the diversity of marine ecosystems, especially the types of coral sponges. The data in this study were collected through direct observation, using the MDLC (Multimedia Development Life Cycle) method to create coral sponges augmented reality applications. Based on the application of the MDLC method to the coral sponges augmented reality application, the augmented reality coral sponges application can be realized and run on android mobile devices with excellent performance. This application has succeeded in bringing up various types of coral sponges in the form of three-dimensional (3D) objects as a form of information and educational media to the users about the importance of keeping the environment clean from marine trash to maintain the sustainability of the marine ecosystem for a better future.